2017
DOI: 10.18632/oncotarget.20341
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits esophageal squamous cell carcinoma-induced angiogenesis by suppressing JAK/STAT3 signaling pathway

Abstract: Although it has been known that the tumor microenvironment affects angiogenesis, the precise mechanism remains unclear. In this study, we simulated the microenvironment of human esophageal squamous cell carcinoma (ESCC) by tumor conditioned medium (TCM) to assess the influence on normal endothelial cells (NECs). We found that the TCM-induced NECs showed enhanced angiogenic properties, such as migration, invasion and tube formation. Moreover, the TCM-induced NECs expressed tumor endothelial cells (TECs) markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…Contrary to the present findings, the CM of hepatocellular carcinoma and esophageal squamous cell carcinoma cells enhanced the tube-formation abilities of ECs (8,35). In another study, the CM from colon and breast cancer cells supported EC tube formation (36).…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the present findings, the CM of hepatocellular carcinoma and esophageal squamous cell carcinoma cells enhanced the tube-formation abilities of ECs (8,35). In another study, the CM from colon and breast cancer cells supported EC tube formation (36).…”
Section: Discussioncontrasting
confidence: 99%
“…Despite technological advances made in combining surgical resection with chemotherapy or radiotherapy, treatment options remain suboptimal due to early local invasion and systemic metastasis . ESCC is a major histological subtype of esophageal carcinoma diagnosed in East Asian countries, especially in China . Previous studies have demonstrated that multiple biological markers may not only facilitate diagnosis and treatment of ESSC but may also help predict early recurrence and clinical outcomes following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin inhibits IL-6-induced cell transition which may be related to the blocking of STAT3 phosphorylation [131]. Metformin also inhibits the nuclear translocation of NF-jB and phosphorylation of STAT3 [132] and the Janus kinase (JAK), STAT3, c-MYC signaling axis [133][134][135]. By downregulating STAT3, Metformin promotes autophagy [136] as discussed earlier [67].…”
Section: Metformin and Cell Transitionmentioning
confidence: 80%